Microwave‐Positioning Assembly: Structure and Surface Optimizations for Catalysts. Issue 3 (17th January 2022) - Xiao, Shuning; Huo, Mengjia; Guan, Yuchuan; Cao, Haiyan; Huang, Qian; Chen, Linglong; Li, Shuangjun; Li, Guisheng; Zhang, Dieqing; Li, Hexing
Abstract : As an innovative synthesis and modification method for nanomaterials, microwave‐positioning assembly exhibits various advantages like low power consumption, oriented growth, and precise doping in preparing and modifying catalysts, mainly owing to the superhot characteristics under microwave irradiation. There are different types of microwave‐positioning assembly mechanisms accounting for the controlling design of the composition, structure, surface chemical state, interface bonding, and some other factors of the catalyst. This review summarizes the recent achievements on the research progress of microwave‐assisted synthesis and modification of new catalysts with the improved performances in various catalytic reactions. The problems and developments of this method in future catalyst design are simply prospected. Abstract : Microwave‐positioning assembly based on the superhot characteristics of specific materials under microwave irradiation exhibits various advantages, such as fast heating, reduced site reaction, oriented nucleation, and growth in composite catalysts synthesis. With these, the novel synthesis method provides an effective way for catalysts optimization, thus enhancing the catalytic performances in the energy and environmental applications.